Oral therapy extension programme: phase 2 - BRAC (© BRAC, 2016)
1. Bangladesh Rural Advancement Committee 2. BRAC medical programme 3. BRAC oral therapy programme 4. Diarrhoea 5. Clinical effects of diarrhoea 6. Development of oral therapy 7. Development of lobon-gur saline 8. Oral therapy education 9. Publicity